Reciprocal impact of mental health and quality of life in children and adolescents—a cross-lagged panel analysis - Wirtz, Markus A.; Devine, Janine; Erhart, Michael; Reiß, Franziska; Böcker, Maren; Schulz, Anja A.; Zöllner, Fionna; Napp, Ann-Kathrin; Ravens-Sieberer, Ulrike; Kaman, Anne (Frontiers in Psychology, 2025)
IntroductionA thorough understanding of the interplay of mental health (MH) and quality of life (QoL) is essential to describe, understand and support the healthy development of children and adolescents. The aim of the study is to analyze the reciprocal and predictive relationship between psychosomatic symptoms, MH problems and QoL in children and adolescents during the COVID-19 pandemic using a cross-lagged panel analysis.MethodsData of n = 323 children and n = 421 adolescents were collected at five measurement points from spring 2020 to autumn 2022 within the population-based longitudinal German COPSY study. Parent proxy ratings were assessed using the KIDSCREEN-10 index (QoL), the Strengths and Difficulties Questionnaire (SDQ; internal and external MH symptoms) and the Health Behavior in School-aged Children Symptom Checklist (HBSC-SCL; psychosomatic symptoms). Adolescents also self-rated the KIDSCREEN-10 Index and the HBSC-SCL. Cross-lagged-panel models, which offer higher internal validity than traditional cross-sectional and longitudinal analyses, were estimated using structural equation modeling (maximum likelihood).ResultsDifferent prediction models proved to be valid for children vs. adolescents (Δχ2df = 48 = 167.84, p < 0.001). For children, QoL did not cross-predict MH indicators (Δχ2df = 12 = 15.53, p > 0.05), but was the time-lagged criterion variable most strongly predicted by them (Δχ2df = 12 = 71.58, p <0.001). For adolescents, self-reported QoL cross-predicted psychosomatic symptoms (Δχ2df = 3 = 14.22, p < 0.001). For both children and adolescents, internalizing MH problems cross-predicted QoL and psychosomatic symptoms (Δχ2df = 3 = 9.58–13.69, p < 0.001).DiscussionPsychosomatic and psychological MH symptoms were proven to be significant time-lagged predictors of QoL, particularly in children. Thus, they can serve as preceding indicators for the development of QoL. Since the cross-lagged panel approach provides a higher internal validity than e.g., cross-sectional data analyses, our findings may contribute to an enhanced understanding of mental development processes and, thus may provide evidence for targeted support of healthy development under demanding conditions such as the COVID-19 pandemic.